Adiabatic preparation of a cold exciton condensate - Shahnazaryan, V. (2015)
We propose a scheme for the controllable preparation of a cold indirect exciton condensate using dipolaritonic setup with an optical pumping. Dipolaritons are bosonic quasiparticles which arise from the coupling between cavity photon (C), direct exciton (DX), and indirect exciton (IX) modes and appear in a double quantum well embedded in a semiconductor microcavity. Controlling the detuning between modes of the system, the limiting cases of exciton polaritons and indirect excitons can be realized. Our protocol relies on the initial preparation of an exciton polariton condensate for the far blue-detuned IX mode, with its subsequent adiabatic transformation to an indirect exciton condensate by lowering IX energy via applied electric field. The following allows for generation of a spatially localized cold exciton gas, on the contrary to currently used methods, where IX cloud appears due to diffusion of carriers from spatially separated electron- and hole-rich areas.